2013
DOI: 10.1177/1363461513512015
|View full text |Cite
|
Sign up to set email alerts
|

A brief anti-stigma intervention for Chinese immigrant caregivers of individuals with psychosis: Adaptation and initial findings

Abstract: Mental illness stigma has adverse effects on both the caregivers’ psychological well-being and the effectiveness of care that consumers receive. While anti-stigma interventions for family caregivers from Western settings have recently shown efficacy, these interventions may not be equally applicable across culturally diverse groups. Specifically, Chinese immigrant caregivers experience heightened internalized stigma, which predisposes the adoption of harmful coping strategies and reduced quality of social netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Other studies used qualitative data obtained from interviews and focus groups involving individuals from the target population, family members, community members, and service providers to identify mental health needs and intervention strategies specific to Asian Americans (Javier et al, 2014; Ling et al, 2014). The intervention programs highlighted the mental health needs of Asian American populations at different developmental periods, as well as those of their family members, from early childhood (Huang et al, 2014), to children/adolescents or mothers with children/adolescents (Javier et al, 2014; Ling et al, 2014; Yeh, Borrero, et al, 2014; Zhou et al, 2014), to caregivers (mother or spouse) of adult patients with mental health disorders (L. H. Yang, Lai, et al, 2014), and to older adults (Jang, Chiriboga, et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies used qualitative data obtained from interviews and focus groups involving individuals from the target population, family members, community members, and service providers to identify mental health needs and intervention strategies specific to Asian Americans (Javier et al, 2014; Ling et al, 2014). The intervention programs highlighted the mental health needs of Asian American populations at different developmental periods, as well as those of their family members, from early childhood (Huang et al, 2014), to children/adolescents or mothers with children/adolescents (Javier et al, 2014; Ling et al, 2014; Yeh, Borrero, et al, 2014; Zhou et al, 2014), to caregivers (mother or spouse) of adult patients with mental health disorders (L. H. Yang, Lai, et al, 2014), and to older adults (Jang, Chiriboga, et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, results of the studies performed by Bernhard et al and Yang et al indicated that training, knowledge, and attitude of the caregivers may improve the mental illness [ 11 , 16 ]. In addition, Cuhadar et al and Cook et al also reached the conclusion that the hiding rate by the caregivers significantly declined post-intervention [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stigma results the feeling of embarrassment in many family caregivers of mental patients. It should be noted that a low percentage of these members undergoes education and sufficient information considering the mental illnesses, signs and symptoms, correct approaches for facing the patients, and stereotyping [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Providers' ability to recognize and help to combat caregivers' self-stigma is essential. In addition to provider-afforded education and consultation about internalized stigma, resources such as Anti-stigma Intervention 55 and In Our Own Voice-Family Companion 56 also demonstrate effects in lowering internalized stigma and empower caregivers with strategies to counter effects of stigma.…”
Section: Discussionmentioning
confidence: 99%